2008
DOI: 10.1128/aem.01696-07
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microbial and Photochemical Processes and Their Combination for Degradation of 2-Aminobenzothiazole

Abstract: The transformation of 2-aminobenzothiazole (ABT) was studied under various conditions: (i) a photodegradation process at a of >300 nm in the presence of an Fe(III)-nitrilotriacetic acid complex (FeNTA), (ii) a biodegradation process using Rhodococcus rhodochrous OBT18 cells, and (iii) the combined processes (FeNTA plus Rhodococcus rhodochrous in the presence or absence of light). The transformation of ABT in the combined system, with or without light, was much more efficient (99% degradation after 25 h) than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
1
16
0
2
Order By: Relevance
“…7). The question remains as to how FeNTA was able to activate the biodegradation of ABT by R. rhodochrous cells observed previously (5). This activation was quite unexpected because no example was reported before, even for other organic compounds in the case of bacteria from the genus Rhodococcus.…”
Section: Vol 74 2008mentioning
confidence: 68%
“…7). The question remains as to how FeNTA was able to activate the biodegradation of ABT by R. rhodochrous cells observed previously (5). This activation was quite unexpected because no example was reported before, even for other organic compounds in the case of bacteria from the genus Rhodococcus.…”
Section: Vol 74 2008mentioning
confidence: 68%
“…Biodegradation pathways of benzothiazole, 2-hydroxybenzothiazole and 2-mercaptobenzothiazole have been elucidated with these Rhodococcus strains ( [Besse et al, 2001], [Haroune et al, 2002] and [Haroune et al, 2004]). In a recent paper, Bunescu et al (2008a) investigated in detail the degradation pathways of 2-aminobenzothiazole (ABT), a compound used as reagent in azo-dye manufactories. They tested various conditions that could occur in the environment: (1) direct photodegradation under sunlight and photo-induced degradation in the presence of Fe(III)-nitrilotriacetic acid (FeNTA).…”
Section: Introductionmentioning
confidence: 99%
“…The biodegradation process led to the accumulation of 6OH-ABT, while the combined processes (biodegradation in the presence of FeNTA with or without exposure to sunlight) produced 6OH-ABT and 4OH-ABT. Apart from the identification of the pathways involved in these different ABT degradation processes, Bunescu et al (2008a) showed a very important feature: the presence of FeNTA, even in the absence of light, improved dramatically the rate of ABT biodegradation. Indeed 99% of ABT was degraded after 25 h in the combined systems while 37% and 26% of ABT were photo-and biodegraded after 125 h, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…La présence d'éléments métalliques de paladium, nickel, cobalt ou fer en faible concentration est reconnue depuis plusieurs années pour accélérer les réactions de biodégradation (Chorao. 2008 ;Bunescu et al, 2008 ;Murugesan et al, 2011). De nombreuses études ont porté sur la biodégradation des polluants en présence de fer sous différentes formes : sels, complexes, nanoparticules (Bunescu et al, 2008, Chorao, 2008Santos et al, 2008 ;Ansari et al, 2008 ;Aldric, 2009).…”
Section: Introductionunclassified
“…2008 ;Bunescu et al, 2008 ;Murugesan et al, 2011). De nombreuses études ont porté sur la biodégradation des polluants en présence de fer sous différentes formes : sels, complexes, nanoparticules (Bunescu et al, 2008, Chorao, 2008Santos et al, 2008 ;Ansari et al, 2008 ;Aldric, 2009). Ansari et al (2008) ont démontré l'impact positif de la présence de nanoparticules de magnétite Fe 3 O 4 sur la cinétique de désulfurisation de dibenzothiophene par Rhodococcus erythropolis IGST8 en augmentant la perméabilité de la membrane vis-à-vis du polluant et des produits de la réaction.…”
Section: Introductionunclassified